HUBUNGAN TERPAAN MEDIA WEBSITE KOMINFO.CO.ID TERHADAP PENGETAHUAN MAHASISWA ILMU KOMUNIKASI UNIVERSITAS SLAMET RIYADI SURAKARTA TENTANG UU ITE - Arif Priadi, Dimas (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2025)
This study aims to thoroughly analyze the relationship between exposure to the official website of the Ministry of Communication and Information Technology (Kominfo.go.id) and the level of knowledge of Communication Science students at Slamet Riyadi University Surakarta (UNISRI) regarding the Electronic Information and Transactions Law (ITE Law). In today’s digital era, the government, through Kominfo, plays a crucial role in providing relevant and accurate access to legal information, particularly the ITE Law, which regulates behavior in cyberspace. Kominfo.go.id has become one of the main platforms used to reach the broader public. This research involved one hundred Communication Science students from UNISRI as respondents. A quantitative research method with a correlational approach was used to test the hypothesis. The results indicate a statistically significant relationship between the level of exposure to the Kominfo.go.id website and the level of knowledge of UNISRI Communication Science students about the ITE Law. The frequency of access and the level of attention paid to the website’s content substantially contribute to the enhancement of students’ cognitive knowledge, especially in terms of understanding and analyzing the content of the ITE Law. This study highlights the importance of effective digital media content management by government institutions to support legal literacy among the public, particularly the younger generation who actively use the internet. The implication of this study is the need for more targeted and interactive communication strategies through government digital platforms to enhance legal awareness in society. Keywords: media exposure, Kominfo.go.id website, digital media, cognitive knowledge, legal literacy, ITE Law, government communication, university students, UNISRI.